2022
DOI: 10.1186/s12931-022-02257-6
|View full text |Cite
|
Sign up to set email alerts
|

Role of the occupational disease consultant in the multidisciplinary discussion of interstitial lung diseases

Abstract: Background Diffuse interstitial lung diseases (ILD) constitute a heterogeneous group of conditions with complex etiological diagnoses requiring a multidisciplinary approach. Much is still unknown about them, particularly their relationship with occupational exposures. The primary objective of this study was to investigate the distribution of occupational exposures according to type of ILD. The secondary objectives were to estimate the proportion of ILDs possibly related to occupational exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In addition to HP, CBD cases may benefit from immunosuppressive treatment. Currently, however, occupational respiratory specialists are not part of the multidisciplinary discussion teams that try to establish the diagnosis and best treatment options for ILD patients [ 51 ].…”
Section: Occupational Interstitial Lung Diseasesmentioning
confidence: 99%
“…In addition to HP, CBD cases may benefit from immunosuppressive treatment. Currently, however, occupational respiratory specialists are not part of the multidisciplinary discussion teams that try to establish the diagnosis and best treatment options for ILD patients [ 51 ].…”
Section: Occupational Interstitial Lung Diseasesmentioning
confidence: 99%
“…Carlier et al. have recently reported that the integration of a specialized occupational consultation in the multidisciplinary evaluation of patients with ILD resulted in a change in diagnosis in 12.8% (18/141) of cases, with 15.6% of patients (22/1141) being eligible to claim compensation for an occupational disease [71]. A diagnosis of occupational ILD carries legal consequences; indeed, once the occupational origin of the disease has been confirmed, patients can claim compensation.…”
Section: Diagnostic Approach To Patients With Suspected Occupational Ildmentioning
confidence: 99%